2018
DOI: 10.7759/cureus.3042
|View full text |Cite
|
Sign up to set email alerts
|

Severe Traumatic Brain Injury Requiring Surgical Decompression in the Young Adult: Factors Influencing Morbidity and Mortality – A Retrospective Analysis

Abstract: Introduction: Severe traumatic brain injury (TBI) is a leading cause of morbidity and mortality among young adults. The clinical outcome may also be difficult to predict. We aim to identify the factors predictive of favorable and unfavorable clinical outcomes for youthful patients with severe TBI who have the option of surgical craniotomy or surgical craniectomy.Methods: A retrospective review at a single Level II trauma center was conducted, identifying patients aged 18 to 30 years with isolated severe TBI wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
2
9
0
1
Order By: Relevance
“…According to the literature, factors associated withmortality are age, the low-GCS score at admission, the size of the craniectomy, effacement of basal cisterns, and severe midline shift. 13 16 22 23 24 Unfavorable outcomes reported were low-GCS scores on admission, postoperative hydrocephalus, tracheostomy, sphenoid fractures, and unchanged ICP. 21 25 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, factors associated withmortality are age, the low-GCS score at admission, the size of the craniectomy, effacement of basal cisterns, and severe midline shift. 13 16 22 23 24 Unfavorable outcomes reported were low-GCS scores on admission, postoperative hydrocephalus, tracheostomy, sphenoid fractures, and unchanged ICP. 21 25 26 …”
Section: Discussionmentioning
confidence: 99%
“… 16 20 21 22 24 25 26 27 In-hospital mortality rates ranged between 32 to 55%, 20 21 26 whereas 30-day mortality rates ranged from 12 to 28.3%. 16 22 24 27 Laghari et al reported an in-hospital mortality rate of 25% at 3 months in their series. In addition, Khalili reported a mortality rate of 40.8% at 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective review on postsurgical outcomes of patients with severe TBI found that individuals presenting with a GCS score of 3-5 were nearly 5 times more likely to have a poor outcome at 30 days compared to patients with a GCS score of 6-8. 16 Cooper et al, in a prospective randomized controlled trial, found that patients with severe TBI receiving decompressive craniectomy compared to the standard level of care had higher odds of unfavorable outcome and similar death rates at 6 months. 4 These previous findings, along with our data, should encourage research on the reprioritization of care to patients with less severe injuries, a drastic change to the traditional practice in which the most severely injured patients are prioritized for care.…”
Section: Impact Of Surgerymentioning
confidence: 99%
“…Studies on adults without any age limit have shown that the 30-day mortality rates ranged from 15.3 to 31.5% 5,6 . In young adults between the ages of 18 and 30 years, the 30-day mortality rate has been reported to be 12% 7 . In this study, 7-and 30-day mortality rates were 20.9 and 44.5%, respectively, which are higher than the rates demonstrated in other studies.…”
Section: Discussionmentioning
confidence: 99%